Facilities management practice in traditional Pondok institution in Malaysia - Ibrahim, Muhammad Shahrol Hafiz; Abdul Talib, Yuhanis; Salleh, Nor Aini; Awang, Mariah; Pangiran Julaini, Pangiran Shafiq (UiTM Press, 2025)
The Pondok educational system, one of the earliest in the Malay Archipelago, focused on Islamic studies. Since then, the development of the Pondok required more attention in many aspects. However, limited studies have been conducted on these issues, mainly due to a lack of awareness regarding the need of proper facilities management in Pondok Institution in Malaysia. This research aims to propose practical strategies to improve facilities management practice in traditional Pondok institutions. There are two objectives for this research. First, to examine the barriers in managing the facilities provided in Pondok institution. Second, to propose practical, effective facilities management in Pondok institution. A quantitative approach is used in this research. The data was collected by using questionnaire surveys to meet the objectives. The result of the study found that a holistic strategic approach to acknowledge the barrier as well as enhance the legislative, management and guidelines are needed for the Pondok institutions to ensure the effectiveness of facilities management planning can be achieved. It is hoped that the study can contribute to the improvement of effective planning of facilities management to the Pondok institutions in Malaysia.